DAMPAK PERKAWINAN SIRRI PADA MASYARAKAT SIPIROK DITINJAU DARI HUKUM KELUARGA - Hamdan Hamdan; Fatahuddin Aziz Siregar; Putra Halomoan Hasibuan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study aims to examine the practice of sirri marriage that occurs in the Sipirok community. One of the goals is to find out the phenomenon of sirri marriage in terms of family law aspects. The type in this research is juridical. While its nature is juridical-normative. Where will view the theories, principles of law and legislation. The data collection methods for this study are observation, interviews and documentation. The results of this study indicate that the practice of sirri marriage that occurs in the Sipirok community is forced. One of the causes is the bride getting pregnant out of wedlock, polygamy, education and not having enough money. According to Islam, that action is legal. Because the pillars and conditions of marriage have been fulfilled. However, according to national law, this act is illegal because it is not registered at the office of religious affairs. One of the impacts is that the marriage is not harmonious because it is often hit by debates and fights in a household. It means not getting peace in the family. Meanwhile, according to family law, that the act is not in accordance with the five principles of the Shari'ah, both aspects of religion, soul, mind, lineage and wealth.